THE ROLE OF THE TEACHER AS A MOTIVATOR IN UPLOADING STUDENT DISCIPLINE AT BOARDING SCHOOLS - Ikhsanuddin, I; Mujiburrohman, M (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to find out how the role of the teacher as a motivator in upholding the discipline of students in Islamic boarding schools. The method used in this research is descriptive qualitative. Qualitative descriptive research aims to describe, describe, explain, explain and answer in more detail the problems to be studied by studying as much as possible an individual, a group or an event. The subjects of this study were teachers and students at Nurul Quran Simo Boyolali Islamic Boarding School. Data obtained through observation, interviews and documentation. Data validation techniques in this study are technique triangulation and source triangulation. While data analysis is divided into several stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that teachers have a significant influence in enforcing the discipline of students. With the activities of observing, asking questions, gathering information, trying to reason and communicate, it is hoped that students will continue to follow the system that has been set by the Islamic boarding school. The factors that influence the discipline of students include; 1) external motivation for students' undisciplined behavior, 2) internal motivation for students' undisciplined behavior, 3) external motivation for students' disciplinary behavior, and 4) internal motivation for students' disciplinary behavior.